Women’s rights under universal protection and international human rights treaties: dialogues between global and local - Taroco, Lara Santos Zangerolame; Colares, Ana Cecília Sabbá (Revista Videre, 2018)
The main international human rights documents establish gender equality as a right to be enforced. Nevertheless, this equality has remained purely formal. The task of transforming it into real equality has been arduous, especially because the historical construction of human rights has always occurred with the exclusion of women and the reinforcement of patriarchal ideologies. The result of this inequality is women’s vulnerability, which directly affects the fulfillment of human rights. Therefore, the proper confrontation of the circumstances that give rise to women’s vulnerability, linked to the promotion of gender equality policies, is essential for human rights international bodies enforcement. This study aims to discuss the main international treaty related to women’s protection, the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), and to analyze how Brazilian legal system incorporates this treaty, which influences our domestic legal order.